Biometrics Security for Secured Login Access by Using Random Fingerprint Recognition Technique - Wan Chik, Rita Zaharah; Muhamad Yasin, Amirul Mukminin (Journal of Computing Technologies and Creative Content, 2017)
Fingerprint recognition system has been implemented for a long time in the security system. The fingerprint is one of the ways to identify a person’s identity because every person has a unique thumbprint. Normally a person used a thumbprint for authentication, but it is not secured anymore nowadays because a thumbprint is way too easy for some people to copy and use it for bad things. The attacker can access the system by steal the thumbprint of the victim. The objective of this research to study about fingerprint recognition in the authentication system, to develop biometric security by using random fingerprint recognition technique and to test the usability of random fingerprint recognition technique. The random fingerprint recognition technique will be developed using a Microsoft Visual Studio 2015 Enterprise (via VB.net programming), Microsoft Access and device Adafruit Optical Fingerprint Sensor. This system is to produce a new level of security that can enhance fingerprint authentication by using random fingerprint recognition technique. Hence, every time the user wishes for passing the security system, the user is needed to do the recognition. The benefit for the company that using this system could control the workplace from an outsider or prevent trespassers from accessing the system because this system is unpredictable and has 2-layer of authentication.